Lone wolf - Picoult, Jodi, 1966- (London : Hodder & Stoughton, 2012)
"When his father and sister are injured in an accident that has rendered his father comatose, estranged son Edward decides to stop his father's life support so that his organs can be donated, a choice his sister urges him to reconsider"--Provided by publisher.
Adult.
Adult
Keywords: Accident victims -- Fiction; Brothers and sisters -- Fiction; Parent and adult child -- Fiction; Terminal care -- Decision making -- Fiction; Accidents -- Fiction; Decision making -- Fiction; Parent-child relationship -- Fiction; Siblings -- Fiction; Terminal care -- Fiction